Knowledge, attitude, and practice of disposal of unused or expired medicines among medical students of South Delhi - Rehman, Sana; Rashid, Mohammad Asim (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Many people are unaware about the disposal of expired medications. Improper disposal and misuse of medicines have major safety and environmental concerns, which makes appropriate disposal practices essential. Objectives were to evaluate the knowledge, attitude, and practice of disposal of unused or expired medications among medical students. Methods: A cross-sectional, questionnaire-based study was conducted among 150 first-year medical undergraduate students. Data were collected using a Google form designed to evaluate knowledge, attitude, and practices related to the disposal of unused and expired medications. Responses were analysed using Microsoft excel (2019 version) and explained in frequencies and percentages. Results: Among the 150 participants, 52% were aged 19-20 years and 56.7% were female. 74.7% were correct that the expiration date was the date after which a medicine becomes unsuitable for use. 20.7% returned unused medicines to medical stores, while 3.3% believed that using expired medicines is illegal. Approximately 19.3% think that unused medicines should be disposed in the red bag. Few (10%) think that the health care system should be responsible for the disposal of unused/expired drugs. The 8.7% consider disposal of aerosol canisters into water bodies. Awareness about the medicine disposal policy in India was low (10.7%). Although 88.7% checked expiry dates before using medicines, improper disposal practices were still observed. The 96.7% required educational programs on safe medication disposal. Conclusions: The study revealed poor awareness among first-year medical students regarding hazards of improper drug disposal. Knowledge gaps led to incorrect practices. WHO guidelines should be implemented, with regular awareness programs promoting safe medication disposal practices.